High Data Rate Wireless Communication Using MIMO - Habib, Sheikh Mohsin (My University, 2010)
Wireless communication is the most popular and rapidly growing sector of the commu-nication industry. The permitted bandwidth for every service is very limited and the demand of data transferring is increasing day by day. Moreover, the channels are further limited by multipath and fading. Hence, it is a big challenge to provide excellent quality of service and meet the growing demand with the existing bandwidth limitation. MIMO is one very promising technique to enhance the data rate. Fading has been considered as problem for high quality with low outage wireless com-munication. However, multiple-input multiple-output (MIMO) antenna has used this fading phenomenon not only to mitigate the fading but also to exploit this fading to obtain high data rate through spatial multiplexing. In this thesis, MIMO spatial multiplexing has been studied in details. Different MIMO channel models, space time coding, and channel capacity constraints as well as the fac-tors those limits the capacity are studied. One major aim of this study is to find a com-bined optimal solution for MIMO system so that it could provide high rate data transfer.
Keywords: MIMO; Space-Time coding; Channel Capacity; Spatial Multiplexing; Capacity Limitation; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|